Influence Of Point And Helix Angle On Thrust Force And Delamination For One-Shot Drilling Of Carbon Fiber Reinforced Plastic (CFRP) - Salleh, Mohd Shukor; Jaafar, Mohd Fairuz; Raja Abdullah, Raja Izamshah; Yahaya, Saifudin Hafiz; Hassan, M.H.; Al-Zubaidi, S.S. (Penerbit UTeM, 2020)
Drilling operation for CFRP parts in the aircraft industry assembly line is unavoidable. Delamination frequently occurs during drilling holes in CFRP and reduces the ability of CFRP parts to carry loads and affects its service life spend. Drill reamer is enhancing the drill bits option for oneshot drilling to save time and cost. This article aims to investigate the influence on the variation of point and helix angle of drill reamer to thrust force and delamination damage. Different drills with the variation of point and helix angle were used to drill unidirectional CFRP laminates panel separately. From the thrust force curve graph, drilling using drill reamer can be divided into three main stages. Point angle geometrical feature influence in stage I while, helix angle in stage III, whereas stage II act as an opener for the drilled hole. Its found that point angle in drill reamer act as pilot drill and helix angle significantly affect to drilled holes quality. Variation of point angle features affected the thrust force measurement for stage I of drilling. The minor righthand side helix angle reduces the delamination compared to straight flute but negatively affected when major helix angle applied. The suitable combination of drill reamers’ geometry features will enhance overall drilling qualities.